A Perspective on Cognitive Research in Accounting. - Hogarth, Robin M. (The Accounting Review, 1991)
The article focuses on cognitive research in accounting (CRA). Auditing is a multifaceted process in which judgment plays a key role. Moreover, CRA studies to date have successfully elucidated several aspects of how auditors make some of these judgments. Most of these studies, however, have focused on particular aspects of audit judgment and have been conducted within specific metaphors of underlying processes. There have been two advantages of this approach. First, the work in CRA has become well grounded in the discipline of psychology, both in terms of theory and methodology. CRA generally demonstrates a high level of professional competence. Second, because auditing is an important professional occupation, results have been illuminating independent of whether they do or do not corroborate earlier findings from psychology. In the future, there will always be a need for good studies that examine specific aspects of judgmental processes in auditing. In the final analysis, however, audits take place in a larger and more complex context than those portrayed in most CRA studies. Indeed, a new goal for CRA is to serve as a role model for how to investigate professional judgment in applied settings.